Investigations On Human Perceptual Maps Using A Stereo-Vision Mobile Robot - Eng, Swee Kheng (2018)
Spatial cognition is a branch of cognitive psychology concerning the acquisition, organization, utilization, and revision of knowledge about spatial environments. A new computational theory of human spatial cognitive mapping has been proposed in the literature, and analyzed using a laser-based mobile robot. In contrast with the well-established SLAM (Simultaneous Localization and Mapping) approach that creates a precise and complete map of the environment, the proposed human perceptual map building procedure is more representative of spatial cognitive mapping in the human brain, whereby an imprecise and incomplete perceptual map of an environment can be created easily. The key steps in the methodology are capturing stereo-vision images of the environment, creating the tracked reference objects (TROs), tracking the number of remaining TROs, and expanding the map when the limiting points of the environment are reached. The main contribution of this research is on the use of computer vision techniques and computational mapping algorithms on a stereo-vision mobile robot for formulating the human perceptual map systematically, and evaluating the resulting human perceptual maps pertaining to both indoor and outdoor environments comprehensively. Validating the human perceptual maps using vision-based techniques is important for two reasons. Firstly, vision plays an important role in the development of human spatial cognition; secondly, computer vision systems are less expensive and information-rich in representing an environment. Specifically, computer vision techniques are first developed for analyzing the associated stereo images and retrieving the displacement information of a mobile robot, as well ascreating the necessary tracked reference objects. A number of computational mapping algorithms are then employed to build a human perceptual map of the environment in this research. Four real-world environments, namely two large indoor and two large outdoor environments, are empirically evaluated. The spatial geometry of the test environments vary, and the environments are subject to various natural effects including reflection and noise. The reflection and noise occurrin many parts of the images. Therefore, additional algorithms are developed in order to remove the reflection and noise. The removal of reflection and noise significantly reduces the number of TROs createdfor every immediate view. The outcomes indicate that the proposed computer vision techniques and computational mapping algorithms for human perceptual map building are robust and useful. They are able to create imprecise and incomplete human perceptual maps with good spatial representation of the overall environments. The map is imprecise and incomplete in the sense that it is not accurate in metric terms and has perceived surfaces missing. It is shown that both vision-based and the laser-based systems are able to computer a reasonably accurate spatial geometry of the tested environment.